Communal Narcissism, Leadership Perception and Leader Selection Recommendations in the Context of Indonesian Collective Culture - Royiqul Amin, Said; Nuzulia, Siti (UMSurabaya Publishing, 2024)
The role of a leader within an organization is crucial for the company's advancement, especially amidst the rapidly changing dynamics of organizations. However, selecting the right leader often remains a primary challenge. Therefore, this research aims to investigate the influence of communal narcissism on leadership perception and leader selection recommendations within Indonesia's collective culture. This study employs a quasi-experimental method, with student activists as participants. Sampling was conducted using convenience sampling, resulting in a total of 416 samples of student activists. The experimental group (n = 236) was tasked with viewing an interview recording of a leadership candidate exhibiting high communal narcissism. In contrast, the control group (n = 180) watched a video recording of a candidate with low communal narcissism. Subsequently, both groups were required to complete a leadership perception questionnaire and provide leader selection recommendations. Data analysis was performed using Independent Sample T-Tests to ascertain differences between the two groups. The research findings reveal significant differences in leadership perception and recommendations between leadership candidates with high and low levels of communal narcissism. Thus, candidates with high levels of communal narcissism were perceived more positively as leaders and were recommended for leadership positions compared to candidates with low levels of communal narcissism